Developing a Warehouse and Distribution Strategy to Manage Global Growth - Allen, David (2011)
With the continuing growth in global business many industries face new challenges, not least within their supply chain network. As the market expands globally so does the complexity of the logistics networks which support both the business and customer requirements, more demanding service levels particularly for lead times and drive for cost reduction are a significant contributor towards the customer’s selection criteria. The literature research aims to understand what challenges global growth presents and the factors that will influence the warehouse and distribution network and shape the strategy in the future. This will provide the author with an insight into the growth and globalisation issues within warehousing and distribution which companies are faced with and enable the comparison and contrast of differing models and approaches being deployed, whilst considering the strategic position the company is taking. Whilst evaluating the Rolls-Royce business model across several sectors the intent is to specifically focus on the challenges within the Civil Aerospace sector as this sector faces comparatively short timeframe in which to deploy a strategy that effectively manages the challenging market growth, the analysis and findings for the Civil sector can then be assessed and taken into consideration as other sectors develop a model. The market growth will impact warehousing and distribution both in support of the production/repair of engine and the aftermarket spares business. To understand the aftermarket ‘service’ expectations there will be a number of interviews with customer facing representatives that will provide valuable information that captures the ‘voice of the customer’ as well as evaluating data on the expected shape of global growth, the business models being contracted and their expectations on service levels. Production growth has seen the capacity issues being addressed through new facilities; in particular the study will evaluate the evolving development of an engine build facility in Singapore and consider the factors and issues faced whilst deploying the warehousing and distribution model to support this facility. Through analysing literature, the Rolls-Royce position, service demands, learning from the Singapore facility development and the UK aftermarket warehousing consolidation project, the study will suggest what needs to be understood when considering how best to effectively plan and execute a warehousing and distribution model and the opportunities within the wider supply chain.